2019
DOI: 10.1088/1748-0221/14/07/p07007
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of a near-infrared (NIR) fluorescence imaging systems intended for hybrid gamma-NIR fluorescence image guided surgery

Abstract: A novel hand-held hybrid optical-gamma camera (HGC) has previously been described that is capable of displaying co-aligned images from both modalities in a single imaging system. Here, a dedicated NIR imaging system for NIR fluorescence surgical guidance has been developed for combination with the HGC . This work has evaluated the performance of two NIR fluorescence imaging systems using phantom studies, various fluorophores and various experimental configurations. The threshold detectable concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The clinical applications of heptamethine cyanine dyes‐related probes mainly focus on ICG and IRDye800CW. ICG has been used for lung metastasis resection of hepatoblastoma, fundus angiography, and lymph node localization, and IRDye800CW is currently in phase II clinical trials in Europe and America (Almarhaby et al, 2019; Yoshida et al, 2021). Yang et al used ICG for NIR fluorescence‐guided uni‐port thoracoscopic segmentectomy (NIF‐VATS; Liu 2020).…”
Section: Applications Of Heptamethine Cyanine Dyes In Clinicmentioning
confidence: 99%
“…The clinical applications of heptamethine cyanine dyes‐related probes mainly focus on ICG and IRDye800CW. ICG has been used for lung metastasis resection of hepatoblastoma, fundus angiography, and lymph node localization, and IRDye800CW is currently in phase II clinical trials in Europe and America (Almarhaby et al, 2019; Yoshida et al, 2021). Yang et al used ICG for NIR fluorescence‐guided uni‐port thoracoscopic segmentectomy (NIF‐VATS; Liu 2020).…”
Section: Applications Of Heptamethine Cyanine Dyes In Clinicmentioning
confidence: 99%
“…The US tissue-like phantom was developed using transparent silicone rubber and fully mixed with other scattering materials (Al 2 O 3 and a cosmetic powder) to mimic the texture and color of human soft tissues. The ratios for mixing these prototype phantom components were 97.52% of silicone rubber, 0.26% of face cosmetic powder, and 2.22% of Al 2 O 3 [23]. The mixture was allowed to slowly fill a Perspex container (length = 10 cm, width = 6 cm, and depth = 8 cm) to avoid the formation of air bubbles within the tissue-like phantom layers.…”
Section: Experimental Validation Of the Proposed Nanotechnology-basedmentioning
confidence: 99%
“…Clinical studies have shown that FGS indeed improves intraoperative tumor detection, regularly leading to a change of the initial surgical plan [8][9][10]. A limitation of using NIRF contrast is the limited NIRF light tissue penetration depth (~ 7 mm) due to photon scattering and absorption, which restricts the ability to visualize deeper-located lesions [11,12]. Although NIRF imaging suffices for visualization of superficial lesions and resection margins, for detection of deeper lesions or resection margins, the combination with an additional real-time technique like photoacoustic (PA) imaging would be beneficial.…”
Section: Introductionmentioning
confidence: 99%